Pengaruh Kepadatan Yang Berbeda Terhadap Kelulushidupan Dan Pertumbuhan Ikan Mas (Cyprinus carpio) Pada Sistem Resirkulasi Dengan Filter Arang - Arisanti, Finly Dwi; Arini, Endang; Elfitasari, Tita (Journal of Aquaculture Management and Technology, 2013)
Common carp (Cyprinus carpio) is a freshwater fish with economical value. High density will result in a limited movement space, higher competition towards oxygen and feed the growth of fish. An increase in density will also decrease the water qualitty One of the efforts to overcome the problem is with the improvement of the environment system by using charcoal filter in recirculation system. The purpose of this research was to explore the influence of different density and the best quantity towards survival rate and growth of common carp (C.carpio) and knowing the effectiveness of charcoal filter on recirculation system. This study was carried out on July to October 2012 at the Laboratory of Aquaculture, Diponegoro University, Semarang. Data obtaired are absolute biomass growth, rate of absolute specifics length, survival rate, ammonia levels, feeding efficiency, and water quality parameters. Experimental research conducted used RAL (completely randomize design) with 3 treatment and 3 replication. Treatment A (10/10 liter), treatment B (15/10 liter), and treatment c (20/10 liter). The result showed that different density has significant effect (P0,05) for survival rate. The different in density absolute biomass growth and survival rate on the best 10 density of fish/10 liter, SR 86,67%±5,77, G 47,42±0,62 g; SGR 2,45±0,04%g/hari; FCR 1,15±0,03, the effectiveness charcoal filter to find ammonia to day 30 a treatment C (20/10 liter) and the measurement of water quality parameters still suitable for Common carp (C. carpio).